ECG-based identification of COPD patients at risk for atrial fibrillation and its impact on adverse clinical outcomes—a subgroup analysis of the prospective multicenter COSYCONET cohort - Eichenlaub, Martin; Frye, Björn Christian; Lehrmann, Heiko; Biertz, Frank; Jadidi, Amir Sherwan; Kaier, Klaus; Melzer, Thomas; Alter, Peter; Watz, Henrik; Waschki, Benjamin; Weckler, Barbara Christine; Trudzinski, Franziska; et al. (Respiratory research, 2025)
Atrial fibrillation (AF) frequently occurs in patients with chronic obstructive pulmonary disease (COPD) and is associated with adverse clinical outcomes. We aimed to identify patients at risk for AF using amplified p-wave duration (APWD) analysis on electrocardiogram (ECG) as non-invasive tool to diagnose an atrial cardiomyopathy (AtCM) which is an established risk factor for AF.